Cryoablation plus chemotherapy regimen enhance anti-tumor immune response in a mouse model of Lewis lung cancer - Hua Duan; Li Yang; Xueni Fang; Shaohua Yan; Yang Cao; Bingli Qiao; Tian Zhou; Kaiwen Hu (International Journal of Hyperthermia)
Background Cryoablation (cryo) is a local anti-tumor method and activation of immunity is one of its mechanisms, but it is affected by many factors. Numerous studies have proved that combination therapy based on cryo can activate immunity more effectively and synergistically. Cryo combined with chemotherapy(chemo) has been proven to improve the quality of life and prolong survival of tumor patients, but the immune effect is still unclear.Methods C57B/L6 mouse lung cancer subcutaneous transplanted tumor model was established and sacrificed at two time points after intervention. We observed the effects of cryo + chemo on survival time, tumor growth, and dynamic changes of immune cells and cytokines.Results Cryo + chemo could not only significantly prolong the survival period of mice, inhibit tumor growth and reduce the proliferation activity of tumor cells, but also promote immune response more effectively. Cryo + chemo could increase the number of CD4+ T cells both in spleen and tumor microenvironment, decrease the infiltration of Treg cells in the tumor microenvironment. Besides, cryo + chemo could increase the expression levels of IL-2 and IFN-γ, and reduce the levels of TGF-β. However, it is worth noting that the immune-promoting effect gradually decreases over time.Conclusions Cryo + chemo can effectively inhibit the growth of lung cancer, prolong the survival period and activate the immune response, providing a theoretical basis for the combined treatment. How to maintain the immune response for a long time is the next problem to be solved.